(untitled) (Journal of Plant Disease Sciences, 2019)
Damping-off caused by Pythium aphanidermatum, in nurseries is a major constraint in chilli production causing plant death, either pre-emergence or post-emergence of seedlings. Present experiment was carried out in in vitro and pot culture to observe the effect of bio-priming with soaking and dry seed treatment with non soaked for bio-agents and metalaxyl against Pythium aphanidermatum. Results revealed that bio-agents, T. harzianum and T. viride recorded maximum mycelial growth inhibition (63.35 and 54.97%, respectively) of the test pathogen and fungicide metalaxyl @ 0.1 and 0.2 per cent was found most effective in inhibition of mycelial growth (100%), of the test pathogen, over untreated control. In seed bio-priming test, significantly least pre-and post-emergence mortality was resulted with metalaxyl (7.40 and 22.22%, respectively), with 76.49 and 76.00 per cent reduction in damping-off incidence, over untreated control, followed by bio-priming with T. harzianum and T. viride.